Description of new sour cherry cultivars and cultivar candidates bred in the Research Institute for the Fruit Growing and Ornamentals - Apostol, J. (International Journal of Horticultural Science, 2008)
Description of new sour cherry cultivars and cultivar candidates bred in the Research Institute for the Fruit Growing and Ornamentals